Kualitas Simplisia Tanaman Biofarmaka Curcuma domestica Setelah Proses Pemanasan Pada Suhu Dan Waktu Bervariasi - Kusumaningrum, Hermin Pancasakti; Kusdiyantini, Endang; Pujiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2015)
Curcuma domestica is one of traditional medicinal plants that is found in Gunungpati Semarang. However the dried product do not achieve optimal standard quality for simplicia  in terms of microbial contaminant and in an industrial scale household. Knowledge on how to use  sterilization   to produce better simplicia and reducing contaminant has not been known by farmers, yet. The purpose of this activity was to obtain the best heating treatment on sterilization of Curcuma simplicia using several temperature under sunlight and oven device. It was also want to  show microbial growth after heating at several times and their  influence on the quality of simplicia after treatment. The method was conducted by  simplicia sterilization of C. domestica using sunlight sterilization for a week and using oven at a temperature of 300C, 400C, 500C and 600C for 1, 3, 6, 9, 12, 24, and 48 hours. The results showed that heating at temperature of 500C for 48 hours obtained the best simplicia, followed by heating at a temperature of 600C for 16-48 hours without contaminants after storing period for 3 months.   Key words :Curcuma, sterilization, heat, microbia